Non-equilibrium properties of an active nanoparticle in a harmonic potential - Falko Schmidt (Nature Portfolio, 2021)
For active particles with nanoscale dimensions the overwhelming rotational diffusivity usually masks their residual non-equilibrium character. Here Schmidt et al. show how to amplify it in a suitable experiment to let a nanosphere rotate spontaneously around the beam axis in an optical trap.